Rhabdochona (Rhabdochona) hypsibarbi n. sp. (Nematoda: Rhabdochonidae) from the freshwater cyprinid fish Hypsibarbus wetmorei (Smith) in northeast Thailand - Moravec, František; Pachanawan, Adithepchaikarn; Kamchoo, Kanda (The Journal of parasitology, 2013)
A new nematode species, Rhabdochona (Rhabdochona) hypsibarbi n. sp. (Rhabdochonidae), is described from the intestine of the freshwater cyprinid fish Hypsibarbus wetmorei (Smith) in the Mekong River, Nakhon Phanom Province, northeast Thailand. It is mainly characterized by medium-sized, bifurcate deirids, the presence of 14 anterior prostomal teeth and distinct basal teeth, length ratio of the muscular and glandular portions of esophagus (1:6-9), length of the left spicule (669-774 μm), absence of a dorsal barb on the right spicule, length ratio of spicules (1:4.9-6.0), arrangement of genital papillae, and smooth eggs without filaments or swellings. In addition, specifically unidentified fourth-stage larvae of Rhabdochona (Rhabdochona) sp., morphologically similar to R. hypsibarbi, were recorded from the red-tailed tinfoil Barbonymus altus (Günther) (Cyprinidae) in the Mekong River, Nakhon Phanom Province, northeast Thailand. Rhabdochona hypsibarbi is the fourth nominal species of Rhabdochona Railliet, 1916 reported from fishes in Thailand and the second species of the nominotypical subgenus found in this country.
Keywords: nemoci ryb; Spiruroidea; střeva; Fish Diseases; larva; Intestines; Female; řeky; Microscopy, Electron, Scanning; Thailand; zvířata; Rivers; Thajsko; infekce hlísticemi řádu Spirurida; ženské pohlaví; Male; mikroskopie elektronová rastrovací; Larva; Animals; mužské pohlaví; Spirurida Infections; Cyprinidae